Regionally Coupled Atmosphere‐Ocean‐Marine Biogeochemistry Model ROM: 2. Studying the Climate Change Signal in the North Atlantic and Europe. (20th August 2020) - Sein, Dmitry V.; Gröger, Matthias; Cabos, William; Alvarez‐Garcia, Francisco J.; Hagemann, Stefan; Pinto, Joaquim G.; Izquierdo, Alfredo; de la Vara, Alba; Koldunov, Nikolay V.; Dvornikov, Anton Yu.; Limareva, Natalia; Alekseeva, Evgenia; et al.
Abstract: Climate simulations for the North Atlantic and Europe for recent and future conditions simulated with the regionally coupled ROM model are analyzed and compared to the results from the MPI‐ESM. The ROM simulations also include a biogeochemistry and ocean tides. For recent climate conditions, ROM generally improves the simulations compared to the driving model MPI‐ESM. Reduced oceanic biases in the Northern Atlantic are found, as well as a better simulation of the atmospheric circulation, notably storm tracks and blocking. Regarding future climate projections for the 21st century following the RCP 4.5 and 8.5 scenarios, MPI‐ESM and ROM largely agree qualitatively on the climate change signal over Europe. However, many important differences are identified. For example, ROM shows an SST cooling in the Subpolar Gyre, which is not present in MPI‐ESM. Under the RCP8.5 scenario, ROM Arctic sea ice cover is thinner and reaches the seasonally ice‐free state by 2055, well before MPI‐ESM. This shows the decisive importance of higher ocean resolution and regional coupling for determining the regional responses to global warming trends. Regarding biogeochemistry, both ROM and MPI‐ESM simulate a widespread decline in winter nutrient concentration in the North Atlantic of up to ~35%. On the other hand, the phytoplankton spring bloom in the Arctic and in the North‐Western Atlantic starts earlier, and the yearly primary production is enhanced in the Arctic in the late 21st century. These results clearly demonstrate the added value of ROM to determine more detailed and more reliable climate projections at the regional scale. Plain Language Summary: We downscale present climate and future climate change projections for the North Atlantic and Europe using a regionally coupled Earth System Model including atmosphere, ocean, river runoff, and ocean biogeochemistry components. This approach allows us to attain higher spatial resolution and to a more accurate representation of key physical processes, yielding a better simulation of present climate at regional and local scales when compared to the driving global climate model. Future climate change projections show more detail at regional and local scale, mostly related to the improvement in the representation of orography and bathymetry. These improvements along with a better representation of the interactive ocean‐atmosphere coupling lead to other remarkable differences with the driving global climate model: (1) colder Sea Surface Temperature in the Subpolar Gyre region, indicating a local convection collapse and a Atlantic Meridional Overturning Circulation slowdown; (2) a seasonal free‐ice Arctic is reached by 2055 under RCP8.5 scenario, well before projected by the driving global climate model; and (3) stronger reduction in nutrients in the North Atlantic by the end of the 21st century. These results clearly demonstrate the added value of the regionally coupled model system to determine more reliable climate projections at the regional scale. Key Points: The regionally coupled model shows reduced oceanic biases in the North Atlantic and a better simulation of the atmospheric circulation The Arctic reaches a seasonally ice‐free state by 2055 with the regionally coupled model under RCP8.5 scenario Changes in biogeochemistry are generally stronger and show enhanced details in the regionally coupled model